2015
DOI: 10.1681/asn.2013101138
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Classification of Autosomal Dominant Polycystic Kidney Disease

Abstract: The rate of renal disease progression varies widely among patients with autosomal dominant polycystic kidney disease (ADPKD), necessitating optimal patient selection for enrollment into clinical trials. Patients from the Mayo Clinic Translational PKD Center with ADPKD (n=590) with computed tomography/magnetic resonance images and three or more eGFR measurements over $6 months were classified radiologically as typical (n=538) or atypical (n=52). Total kidney volume (TKV) was measured using stereology (TKVs) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

22
669
5
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 506 publications
(728 citation statements)
references
References 33 publications
22
669
5
4
Order By: Relevance
“…It was reported that total kidney volume calculated using the ellipsoid equation (TKVe) is strongly correlated with total kidney volume measured by stereology (TKVs) without systematic underestimation or overestimation. 36 It was also reported that the difference between TKVe and TKVs exceeded 10% in ,30% of their patients and exceeded 20% in ,6%. TKVe might be less accurate in patients with large cysts than in patients without large cysts, but the difference between TKVe and TKVs did not exceed 15% in our 12 patients who had large cysts with wall thickening.…”
Section: Discussionmentioning
confidence: 95%
“…It was reported that total kidney volume calculated using the ellipsoid equation (TKVe) is strongly correlated with total kidney volume measured by stereology (TKVs) without systematic underestimation or overestimation. 36 It was also reported that the difference between TKVe and TKVs exceeded 10% in ,30% of their patients and exceeded 20% in ,6%. TKVe might be less accurate in patients with large cysts than in patients without large cysts, but the difference between TKVe and TKVs did not exceed 15% in our 12 patients who had large cysts with wall thickening.…”
Section: Discussionmentioning
confidence: 95%
“…Although the reasons for this favorable prognosis are unclear, some of them may have atypical PKD with unilateral, segmental, or asymmetric cystic involvement, which has been reported to be associated with stable kidney function. 22 Other patients with de novo disease and markedly asymmetric cystic kidney involvement may have somatic mosaicism. The hallmark of mosaicism is the presence of more than one genetically distinct cell line in the affected subject whose disease is invariably mild or focal because of dilution of the mutant gene dosage at the tissue level.…”
Section: Discussionmentioning
confidence: 99%
“…However, this cross-sectional imaging approach is more difficult and requires more timeconsuming processes in image analysis than using ultrasound imaging. A simple but less precise approach of approximating kidney volume from CT or MR images uses the ellipsoid formula that is on the basis of the multiplication of three orthogonally measured longest dimensions of kidney (Supplemental Appendix 2) (22). In a typical clinical setting, the kidney volume from CT or MR images is measured manually by a trained expert who delineates the kidney border over the CT or MR images.…”
Section: Discussionmentioning
confidence: 99%